Analisis belajar mandiri mahasiswa pada pembelajaran online - yubali ani; Mursining Kusuma Wardhani (Jurnal Pendidikan Nusantara, 2022)
Independent learning when online learning is carried out by the entire community in the field of education. The occurrence of the COVID-19 pandemic has had the impact of change for the sake of change, and this in particular, affects the way students learn. Students are required to study independently from their respective homes with limited facilities and infrastructure. The aims and objectives of this research are to find out: 1) the difficulties of independent learning in online learning, and 2) solutions in dealing with difficulties in online learning. This study used a survey approach using questionnaires, data analysis techniques used percentages, and the research subjects consisted of 30 students. The results obtained are: 1) the difficulty of independent learning experienced by students from internal factors, namely students still rarely set learning goals and strategies in online learning, so this makes them not optimal for independent study. Meanwhile, from external factors, namely the lack of facilities and infrastructure that can be used by students to study independently; and 2) independent learning solutions carried out by students, namely: discussing with friends, and asking the teacher when they do not understand the material being studied.